Acquisition of higher-order experimental skills through remote and virtual laboratories - Restivo, Maria Teresa (2019)
Remote laboratories are physical spaces with real apparatus and real instruments connected to the Internet. They allow both students and teachers to remotely conduct real experiments through a simple web browser.